Comparison of Nanomaterials for Enhanced Oil Recovery in Tight Sandstone Reservoir - Zhang, Chenjun; Jin, Xu; Tao, Jiaping; Xiong, Bo; Pan, Zhijian; Meng, Siwei; Ding, Bin; Wang, Ying; Liang, Lihao (Frontiers in Earth Science, 2021)
With dwindling conventional oil resources, the development of high-performance oil-displacing agents to exploit unconventional oil and gas resources has become a research focus, and new technical ideas have been proposed for petroleum engineering with the advancement of nanomaterials and technology. This study characterized the microscopic pore throat structure of the unconventional tight sandstone reservoir of Ordos Basin in China comprehensively by using high-resolution scanning electron microscopy, image panoramic mosaic technology, mineral quantitative scanning system, and 3D image of pore. A new nanofluid with diphenyl ether surfactants as shell and C10–C14 straight-chain hydrocarbon compounds as kernel was prepared according to the features of tight sandstone reservoirs. The basic physical properties of the nanofluid were evaluated and compared with those of three other generic oil-displacing agents to understand the oil-displacement effect and mechanism. Results show that this nanofluid remains relatively stable and dispersible with aging and its average particle size matches well with the pore throat size of the target reservoir, which increases the sweep volume effectively. Additionally, the change from oil-wet to water-wet can exert capillary imbibition. And the oil-water interfacial tension can be greatly reduced to the level of 10−2 mN/m because of nanofluid’s excellent interfacial activity, which improves the efficiency of oil washing in nano-scale pore throats. Finally, the core imbibition experiment further demonstrated the superiority of the nanofluid. Using the nanofluid in optimal concentration with cores of approximately 0.1 mD can achieve a recovery rate of 37.5%, which is higher than generic oil-displacing agents by up to 9%. This study demonstrates that the excellent performance of nanofluid in enhancing oil recovery and provides a reference for the development of unconventional reservoirs, which are difficult to function with generic agents.